2017
DOI: 10.15376/biores.12.4.9366-9382
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on chemical composition, physical, tensile, and thermal properties of sugar palm fiber (Arenga pinnata) obtained from different geographical locations

Abstract: Physical, mechanical, chemical, and thermal properties of sugar palm (Arenga pinnata) fiber were investigated for specimens obtained from three different locations: Kuala Jempol (Peninsular Malaysia), Tawau (West Malaysia), and Tasik Malaya (Indonesia). The morphology of the fiber were observed through scanning electron microscopy (SEM), the thermal properties by thermogravimetric analysis (TGA), tensile properties according to ASTM D3379, and chemical analysis by using neutral detergent fiber (NDF) and acid d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 21 publications
3
12
0
Order By: Relevance
“…Therefore, water absorption and thickness swelling on natural fiber reinforced composites are important factors to be considered in product applications. These results were supported by previous findings on single fibers, in which the relationships between holocellulose content and water absorption affect behaviour (Huzaifah et al 2017). Previous research has indicated that SPF obtained from Kuala Jempol has the highest holocellulose content (54.5%) that contributes to the highest water absorption (161.96 ± 34.04%), followed by Tawau and Indonesia, as shown in Table 4.…”
Section: Physical Properties Of Spf/ve Composites Water Absorption An...supporting
confidence: 88%
See 4 more Smart Citations
“…Therefore, water absorption and thickness swelling on natural fiber reinforced composites are important factors to be considered in product applications. These results were supported by previous findings on single fibers, in which the relationships between holocellulose content and water absorption affect behaviour (Huzaifah et al 2017). Previous research has indicated that SPF obtained from Kuala Jempol has the highest holocellulose content (54.5%) that contributes to the highest water absorption (161.96 ± 34.04%), followed by Tawau and Indonesia, as shown in Table 4.…”
Section: Physical Properties Of Spf/ve Composites Water Absorption An...supporting
confidence: 88%
“…2 below, the SPF Jempol/VE recorded the highest percentage of water absorption and thickness swelling, and this was followed by SPF Tawau/VE and SPF Indonesia/VE. As shown in Table 3, these results were supported by previous research on single fiber tensile tests in which Kuala Jempol fiber had the highest water absorption, 161.96 ± 34.04%, while Tawau and Indonesia were 156.56 ± 19.64% and 80.32 ± 13.3%, respectively (Huzaifah et al 2017). According to Sahari et al (2011), water absorption, thickness swelling, and moisture content are affected by the hydrophilic behavior of the natural fibers and not by the hydrophobic behavior of the polymers.…”
Section: Physical Properties Of Spf/ve Composites Water Absorption An...supporting
confidence: 83%
See 3 more Smart Citations